A filmmaker's guide to sound design : bridging the gap between filmmakers and technicians to realize the storytelling power of sound /: bridging the gap between filmmakers and technicians to realize the storytelling power of sound. (2023) - Rea, Peter W; Polis, Matthew
No abstract available